Analisis Penguasaan Konsep Hasil Pembelajaran Discovery Learning Dengan Bantuan LKS-Induktif Pada Materi Kekuatan Asam Dan Basa Kelas XI MIPA 3 SMA Negeri 3 Palangka Raya Tahun Ajaran 2022/2023 - Safutri, Dita Ika; Abudarin, Abudarin; Asi, Nopriawan Berkat (Jurnal Ilmiah Kanderang Tingang, 2025)
This study aims to describe the concept mastery of students in class XI MIPA 3 of SMA Negeri 3 Palangka Raya through discovery learning assisted by inductive student worksheets (LKS-Induktif). The subjects of this study were students of class XI MIPA 3 who had not yet received the sub-topic on acidity level (pH). The instruments used in this research included a concept mastery test (pretest and posttest) in the form of 5 essay questions, a learning management observation sheet, and a student response questionnaire. The data obtained were analyzed descriptively. The results of the data analysis showed: a) The average concept mastery on the indicator of explaining the definitions of strong acid, weak acid, strong base, and weak base increased by 33.8%, b) The average concept mastery on the indicator of calculating the pH of strong acid solutions based on concentration data increased by 52.3%, c) The average concept mastery on the indicator of calculating the pH of strong base solutions based on concentration data increased by 48.5%, d) The average concept mastery on the indicator of analyzing the pH of weak acids based on concentration data and acid dissociation constant (Ka) increased by 63.5%, e) The average concept mastery on the indicator of analyzing the pH differences of weak base solutions based on concentration data and base dissociation constant (Kb) increased by 83.8%.